Analisis Kinerja Simpang Bersinyal untuk Meningkatkan Keselamatan pada Simpang Depok Kota Depok - Widyawan, Sony; Rukman (Politeknik Penerbangan Makassar, 2019)
The problem of transportation is one of the problems faced in Depok, especially at intersections. Problems of traffic congestion and conflicts often occur at signalized intersections, especially at the intersection of four signalized Depok Depok City where one of the efforts made to reduce conflicts in Depok intersection is done by setting the intersection. The methods used in the analysis of the performance of the intersection is the use of calculation on IHCM, while the traffic conflict analysis to determine the level of seriousness of traffic conflicts is by using traffic conflict Technique (TCT) is compared to that conflict VisSim 10.Recommendation is done by using a scheme using a 3-phase elections and 3.5 phase and then make a comparison with the third phase (existing) and selected the most appropriate scenario. From the scheme of recommendations that were made by using the software PTV VISSIM 10 obtained the most appropriate scheme that uses three-phase arrangement. The results of the simulation phase 3 was effective at reducing the number of traffic conflicts and service levels are still in good condition.